2015
DOI: 10.1007/s12161-015-0266-8
|View full text |Cite
|
Sign up to set email alerts
|

A Modified and Improved Assay Based on Microbial Test System (MTS) to Evaluate Antioxidant Activity

Abstract: An assay based on microbial test system (Escherichia coli) was developed to evaluate the antioxidant capacity of phytochemicals, extracts of plants, fruits, and vegetables. E. coli was cultured in Luria-Bertani (LB) medium. Quercetin was used as a standard in microbial test system (MTS) assay because it had high antioxidant activity and was easily and economically obtained. The cultivation times of E. coli entrance into mid-log phase, before and after H 2 O 2 addition for MTS assay were investigated, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Escherichia coli were used to determine the antioxidant activity of extracts based on the method described by Smirnova and Zhou [ 35 , 36 ]. The bacteria were incubated in Luria—Bertani (LB) medium at 37 °C with shaking at 120 r/min overnight until they reached the midlog phase.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Escherichia coli were used to determine the antioxidant activity of extracts based on the method described by Smirnova and Zhou [ 35 , 36 ]. The bacteria were incubated in Luria—Bertani (LB) medium at 37 °C with shaking at 120 r/min overnight until they reached the midlog phase.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The model of DPPH and ABTS radical scavenging is a widely used method to evaluate the free radical scavenging ability of natural substances. The antioxidant activity of a compound can be presented as its ability to scavenge the radicals by measuring the decline in the absorbance (Zhou et al 2016). As seen in Table 3, the results indicated that the scavenging activity was in the order Rf [ Me [ Df [ Co [ Es. The ABTS radicals were generated by potassium persulfate and have a blue-green chromophore with a maximum absorption at 734 nm, which decreases in intensity in the presence of antioxidants.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…To circumvent the limitations of the assays based on chemical mechanism to determine antioxidant synergistic effects, the MTS assay was adopted to measure the bioavailability behind synergism with some modification [27]. Bacteria were cultivated aerobically overnight in LB medium in shaking bed (37 °C, 120 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…However, the observation in antioxidant synergistic effects of P. fruticosa combined with EGb is still not enough to guide in-depth pharmaceutical applications of P. fruticosa . This experiment carried on the modified and improved assay based on microbial test system (MTS) in our lab [27], focused on the physiological bioavailability to further confirm the synergistic effects of P. fruticosa combined with EGb and try to find specific combinations with least concentrations that exhibit synergistic effects. Those compounds may help to produce natural and safe antioxidants products in lower doses instead of synthetic antioxidants.…”
Section: Introductionmentioning
confidence: 99%